Testosterone and Gonadotropins in Infertile Men with Sertoli Cell Only Syndrome from Gaza Strip - Yassin, Maged M; Lubbad, Abdel Monem H; Taha, Ahmed Z; Laqqan, Mohammed M; Jamiea, Samar M Abu (Journal of Medicine, 2017)
Aim: To assess serum testosterone and gonadotropins in Sertoli cell only syndrome patients from Gaza Strip. Methods: Based on testicular biopsy, a cross section of 74 Sertoli cell only syndrome patients were enrolled in the study. Age matched 44 fertile men were served as controls. Patients and controls were questioned for their medical history. Blood samples were drawn and serum testosterone, luteinizing hormone (LH), and follicle stimulating hormone (FSH) were determined by enzyme-linked immunosorbent assay. Data were computer analyzed using SPSS/PC, version 18.0. Results: Varicocele and hormonal problems were significantly more frequent among patients than controls (P<0.05). Serum testosterone was significantly lower in patients compared to controls (1.7±1.3 versus 5.0±2.2 ng/ml, P=0.000). In contrast, LH and FSH were significantly higher in patients than controls (12.8±9.7 and 20.8±14.8 mlU/ml versus 6.3±3.1 and 7.7±3.9 mlU/ml, P=0.000, respectively). Hypergonadotrophic hypogonadism and hypogonadotrophic hypogonadism patients showed lower levels of testosterone compared to the normal reference value (0.9±0.5 and 0.5±0.4 ng/ml versus 2.0-7.0 ng/ml). Higher levels of LH and FSH were recorded in hypergonadotrophic hypogonadism (24.5±2.6 and 37.4±6.7 mlU/ml) compared to the reference values of 2.0-13.0 and 2.5-10.0 mlU/ml, respectively whereas LH and FSH levels were lower in hypogonadotrophic hypogonadism (0.6±0.4 and 0.6±0.5 mlU/ml, respectively). In this context, all hypergonadotrophic hypogonadism and hypogonadotrophic hypogonadism patients showed abnormal levels of testosterone, LH and FSH. Conclusions: Abnormal levels of serum testosterone, LH and FSH, particularly in hypergonadotrophic hypogonadism and hypogonadotrophic hypogonadism were identified in infertile men with Sertoli cell only syndrome from Gaza Strip. J MEDICINE January 2017; 18 (1) : 21-26